Attentional Biases and Recognition Accuracy: What Happens When Multiple Own- and Other-Race Faces are Encountered Simultaneously?. (January 2015) - Semplonius, Thalia; Mondloch, Catherine J
Adults recognize own-race faces more accurately than other-race faces. We investigated three characteristics of laboratory investigations hypothesized to minimize the magnitude of the own-race recognition advantage (ORA): lack of competition for attention and instructions that emphasize individuating faces during the study phase, and a lack of uncertainty during the test phase. Across two experiments, participants studied faces individually, in arrays comprising multiple faces and household objects, or in naturalistic scenes (presented on an eye-tracker); they were instructed to remember everything, memorize faces, or form impressions of people. They then completed one of two recognition tasks—an old/new recognition task or a lineup recognition task. Task instructions influenced time spent looking at faces but not the allocation of attention to own- versus other-race faces. The magnitude of the ORA was independent of both task instructions and test protocol, with some modulation by how faces were presented in the study phase. We discuss these results in light of current theories of the ORA.